More-Than Human Centred Design: Considering Other Things - Coulton, Paul; Lindley, Joseph Galen (The Design journal, 2019)
This paper responds to contemporary design contexts that frequently contain complex interdependencies of human and non-human actants. To adequately represent these perspectives requires a shift towards More-Than Human Centred Design. The Internet of Things (IoT) is one context that demonstrates this need. The 'things' within such networks transcend their physical forms and extend to include algorithms, humans, data, business models, etc. and each imports independent-but-interdependent motivations and perspectives. Therefore, we use the IoT to clarify our proposition and to convey our three contributions. First, we review the expanding corpus of contemporary Human-Computer Interaction research that seeks to expand the notion of Human Centred Design by moving beyond the dominant anthropocentric perspective. Second, we introduce a novel design metaphor, 'constellations', which allows both the interdependencies and independent perspectives to be considered. Third, we provide an account of a speculative design to demonstrate how it may be put into practice.